2011
DOI: 10.1007/s00216-011-4819-4
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic detection of physiology changes in plasmid-bearing Escherichia coli with and without antibiotic treatment

Abstract: Bacterial resistances against antibiotics are increasingly problematic for medical treatment of pathogenic bacteria, e.g., in hospitals. Resistances are, among other genes, often encoded on plasmids which can be transmitted between bacteria not only within one species, but also between different species, genera, and families. The plasmid pDrive is transformed into bacteria of the model strain Escherichia coli DH5α. Within this investigation, we applied micro-Raman spectroscopy with two different excitation wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 38 publications
0
56
0
Order By: Relevance
“…Since in the literature it has been reported that no single classifier is best for all problems and no classifier is always better than another one (39), we decided to perform a comparative study of two known algorithms practicable for bacterial discrimination (46,54).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in the literature it has been reported that no single classifier is best for all problems and no classifier is always better than another one (39), we decided to perform a comparative study of two known algorithms practicable for bacterial discrimination (46,54).…”
Section: Resultsmentioning
confidence: 99%
“…Although the resonant excitation in the UV wavelength region probes taxonomic markers, e.g., DNA/RNA vibrations (28,48), the application of visible or NIR Raman excitation wavelengths allows for a phenotypic characterization (20). By applying micro-Raman spectroscopy, even bacterial identification on the single-cell level can be performed (8,15,43,54), and thus elaborate precultivation can be avoided. Thus, the detection process of microorganisms can be accelerated significantly, which is especially important in areas susceptible to bacterial contamination, e.g., clinical environments or the food-processing industry.…”
mentioning
confidence: 99%
“…Nonetheless, the relatively few articles published to date on the topic point to a significant potential for Raman spectroscopy to become a powerful tool aiding antibiotic drug research. First, it has been shown that Raman spectroscopy can distinguish between bacterial strains resistant and sensitive to a specific antibiotic (22,26). For example, Maquelin et al (22) used Raman spectroscopy with an 830-nm excitation wavelength to analyze Enterococcus faecalis strains sensitive and resistant to vancomycin.…”
mentioning
confidence: 99%
“…Peaks at 1,580, 1,383, 1,342, 1,321, 1,139, 1,097, 812, and 660 cm Ϫ1 in the SERS spectra of E. coli (Fig. 3) are commonly assigned to DNA, RNA, or their components (7,9,13,19,21,24). These peaks either (i) shifted, (ii) were significantly reduced in intensity, or (iii) were not present when the pgSERS probes were used.…”
mentioning
confidence: 99%
“…The shoulder at 719 cm Ϫ1 in the pgSERS spectrum corresponds to C-C-Nϩ symmetric stretching in phosphatidylcholine, a major constituent of cellular membranes (9). The peak at 744 cm Ϫ1 has been attributed to the membrane-bound cytochromes, hemoproteins that contain heme groups and carry out electron transport (19,23).…”
mentioning
confidence: 99%